Comparative assessment of smartphone‐based digital planimetry for wound area measurement - Sharun, Khan; Banu, Shajahan A.; Mamachan, Merlin; Vinodhkumar, Obli R.; Manjusha, Kallemuchikal M.; Kumar, Rohit; Pawde, Abhijit M.; Dhama, Kuldeep; Pal, Amar (Narra Sains Indonesia, 2025)
Accurate wound area measurement is essential for effective wound care as it helps determine the progression of healing in patients. The aim of this study was to compare two wound area measurement techniques wound tracing (manual planimetry) and imitoMeasure (smartphone-based digital planimetry) with standard ImageJ-based digital image analysis in a rabbit wound healing study. The study involved 291 wounds categorized into small, intermediate, and large wounds. ImageJ was used as the reference method for comparisons. The intraclass correlation coefficient (ICC) was computed to assess the agreement and reliability between different wound measurement techniques. A mountain plot was used to assess the agreement between measurement methods, and a Bland-Altman plot was used to evaluate the agreement and concordance between measurement methods. The time required for analysis (processing time) was also compared. The study revealed that the imitoMeasure consistently demonstrated a greater level of agreement with ImageJ, especially in small and intermediate wounds. The ICC values indicated substantial agreement between ImageJ and imitoMeasure, with an exceptionally high ICC value for small wounds. Mountain plots revealed that the imitoMeasure had better agreement with ImageJ across all wound sizes. Bland-Altman plots further supported these findings, with wound tracing exhibiting wider limits of agreement and greater variability than imitoMeasure. ImitoMeasure consistently proved to be the quickest method across all wound sizes, whereas wound tracing required the longest processing time. These findings indicate that the imitoMeasure is a more reliable and consistent method for measuring the wound area, in particular for small and intermediate wounds.